"Gallstone Hip" and Other Sequelae of Retained Gallstones. Issue 3 (1997) - Chin, Peter T.; Boland, Stuart; Percy, John P.
Abstract : The fate of gallstones spilled during laparoscopic cholecystostomy has been thought to be relatively benign. Recent experience and a review of the recent literature shows that this is not always the case. We report three cases of complications of retained stones and analyse the literature with regard to types of complications, time to presentation, and recommendations for managing spilled gallstones. Retained gallstones have been shown to cause adhesions in the rat and inflammatory reactions in dogs with no evidence of absorption. The average time to presentation of complications arising from retained gallstones is 27.3 weeks. Complications include: Intraabdominal abscess formation with or without abdominal wall sinus tract formation, persisting abdominal wall sinus tracts from port site abscess, subhepatic inflammatory masses, cholelithoptysis, microabscesses and granuloma formation, liver abscess and "dumbell" shaped abscess with one side of the "dumbell" forming a subcutaneous abscess. We recommend the judicious use of retrieval devices during the extraction phase of the laparoscopic cholecystectomy, diligent removal of any spilled stones and awareness of delayed postoperative pain and tenderness as a harbinger of symptomatic retained gallstones. Documentation of intraoperative gallstone spillage, volume, type of gallstones, and effort to retrieve is recommended.